2017
DOI: 10.1111/jmp.12282
|View full text |Cite
|
Sign up to set email alerts
|

Mucosal bacterial dissemination in a rhesus macaque model of experimental brucellosis

Abstract: Animals were experimentally infected with Brucella melitensis via aerosol. B. melitensis was cultured from the saliva and vaginal vault of infected animals, corresponding to bacterial dissemination in other target tissues. This is the first report of bacterial dissemination to these mucosal surfaces in a non-human primate model of brucellosis. K E Y W O R D Saerosol exposure, Brucella melitensis, mucosal dissemination, rhesus macaque

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 16 publications
2
6
0
Order By: Relevance
“…In our experiments, the B. neotomae infectious course in BALB/c mice showed similarity to B. abortus, B. melitensis, and B. suis infection of domesticated farm animals and primates. For example, during aerosol infection of rhesus monkeys with B. melitensis with inocula ranging generally from 10 5 to 6 ϫ 10 6 organisms, both liver and spleen CFU were prominent early in infection (27)(28)(29); liver counts dropped from 10 6 to 10 4 CFU from days 15 to 45 (29); and organisms were isolated at low levels from liver and spleen 8 to 9 weeks after infection (27,28), similar to observations in the B. neotomae murine model. Additionally, significant quantities of organisms were isolated from lymph nodes during B. melitensis infection of rhesus monkeys; during B. abortus strain 1308 and/or 544 McEwen infection of cows and bison (30)(31)(32); and during human infection, especially in children (33,34).…”
Section: Discussionsupporting
confidence: 61%
“…In our experiments, the B. neotomae infectious course in BALB/c mice showed similarity to B. abortus, B. melitensis, and B. suis infection of domesticated farm animals and primates. For example, during aerosol infection of rhesus monkeys with B. melitensis with inocula ranging generally from 10 5 to 6 ϫ 10 6 organisms, both liver and spleen CFU were prominent early in infection (27)(28)(29); liver counts dropped from 10 6 to 10 4 CFU from days 15 to 45 (29); and organisms were isolated at low levels from liver and spleen 8 to 9 weeks after infection (27,28), similar to observations in the B. neotomae murine model. Additionally, significant quantities of organisms were isolated from lymph nodes during B. melitensis infection of rhesus monkeys; during B. abortus strain 1308 and/or 544 McEwen infection of cows and bison (30)(31)(32); and during human infection, especially in children (33,34).…”
Section: Discussionsupporting
confidence: 61%
“…which is similar to human brucellosis, in which the Brucella location in the male reproductive tract is observed in approximately 2% to 10% of reported cases. In other study, B. melitensis was cultured from the saliva and vaginal vault of infected animals, demonstrating bacterial dissemination to other target tissues [39]. Infection with aerosolized B. melitensis only generates changes in some clinical laboratory parameters, such as an increase in C-reactive protein and in certain liver enzymes, which is consistent with what has been observed in human brucellosis [37].…”
Section: Course Of Respiratory Brucella Infection In Animal Modelssupporting
confidence: 79%
“…Like other Gram-negative organisms, Brucella strains express a lipopolysaccharide (LPS) lacking endotoxin activity. Importantly, BmΔ vjbR has been shown to be safe in immunocompetent and immunocompromised mice 9 , goats 10 , sheep 11 , and non-human primates 12 . We also have shown that BmΔ vjbR can combat cancer in a murine model by remodeling the tumor microenvironment (TME) to a pro-inflammatory state 8 .…”
Section: Mainmentioning
confidence: 99%